Usability Testing Vision Sensor Based Work Time Measurement Technology - Euis Nina Saparina Yuliani; Ajeng Yeni Setianingrum; Muhammad Kholil (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2020)
A product or technology is perceived easily in case it has a high level of usability. This means users have no difficulties or encounter problems while using. The purpose of this study is to conduct usability testing of vision sensor-based working time measurement technology. It is meant to determine the ability of the technology to conduct work time measurement functions with the same results as the conventional process using a stopwatch. The study involves an experimental method with two factors. Based on the results of the ANOVA Two-Way Analysis (within-subject design), the first and second levels in apparatus factor shows there is no difference in the average value of the cycle time between work measurements with and without the vision sensor technology (Fobtained(4,1) < Fcritical(5,12)). Therefore, the technology designed is capable of measuring the same work as manual measurement.